Rosai-Dorman disease mimicking lymphoma on 18F-FDG PET/CT - Sharjeel Usmani; Dalal al Turkait Ahmed; Rehab S. Elhaggracy; Karen Pinto; Fareeda al Kandari (Journal of the Pakistan Medical Association, 2022)
Rosai-Dorman Disease (RDD) is an uncommon benign disorder of proliferative histiocytes. RDD is usually self-remitting yet has been shown to mimic lympho-proliferative disorders clinically as well as on imaging studies. We report a-47-year-old female who was referred to our department with the presenting complaint of bulky abdominopelvic nodal masses suspicious of lymphoma where 18F-FDG PET/CT played a role in the evaluation and staging. Keywords: 18F-FDG PET-CT, Rosai-Dorman Disease, Diffuse Large B-Cell Lymphoma